Cholesterol-Binding Sites in GIRK Channels: The Devil is in the Details - Rosenhouse-Dantsker, Avia (Lipid Insights, 2018)
In recent years, it has become evident that cholesterol plays a direct role in the modulation of a variety of ion channels. In most cases, cholesterol downregulates channel activity. In contrast, our earlier studies have demonstrated that atrial G protein inwardly rectifying potassium (GIRK) channels are upregulated by cholesterol. Recently, we have shown that hippocampal GIRK currents are also upregulated by cholesterol. A combined computational-experimental approach pointed to putative cholesterol-binding sites in the transmembrane domain of the GIRK2 channel, the primary subunit in hippocampal GIRK channels. In particular, the principal cholesterol-binding site was located in the center of the transmembrane domain in between the inner and outer α-helices of 2 adjacent subunits. Further studies pointed to a similar cholesterol-binding site in GIRK4, a major subunit in atrial GIRK channels. However, a close look at a sequence alignment of the transmembrane helices of the 2 channels reveals surprising differences among the residues that interact with the cholesterol molecule in these 2 channels. Here, we compare the residues that form putative cholesterol-binding sites in GIRK2 and GIRK4 and discuss the similarities and differences among them.